2011
DOI: 10.1530/erc-11-0335
|View full text |Cite
|
Sign up to set email alerts
|

The renin–angiotensin system in the breast and breast cancer

Abstract: Much evidence now suggests that angiotensin II has roles in normal functions of the breast that may be altered or attenuated in cancer. Both angiotensin type 1 (AT1) and type 2 (AT2) receptors are present particularly in the secretory epithelium. Additionally, all the elements of a tissue renin-angiotensin system, angiotensinogen, prorenin and angiotensin-converting enzyme (ACE), are also present and distributed in different cell types in a manner suggesting a close relationship with sites of angiotensin II ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 227 publications
2
59
0
Order By: Relevance
“…But others, such as the renin-angiotensin system (RAS), which is known for controlling the homeostasis of the organism and not for any apparent involvement in cancer, are now being added to the complex networks of carcinogenesis. 3 The RAS was first discovered and extensively studied in the physiological regulation of systemic arterial pressure and, therefore, in the pathogenesis of hypertension. 4 As a gatekeeper system, RAS is involved in more than one function.…”
Section: Introductionmentioning
confidence: 99%
“…But others, such as the renin-angiotensin system (RAS), which is known for controlling the homeostasis of the organism and not for any apparent involvement in cancer, are now being added to the complex networks of carcinogenesis. 3 The RAS was first discovered and extensively studied in the physiological regulation of systemic arterial pressure and, therefore, in the pathogenesis of hypertension. 4 As a gatekeeper system, RAS is involved in more than one function.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 The 2 main bioactive peptides of the RAS, Ang II and its direct metabolite Ang III, exhibit the same affinity for type 1 and type 2 angiotensin receptors, 20,21 and it is known that AT1 and AT2 receptors are expressed in breast cancer. 8 In this work, the influence of dietary fat on aminopeptidase activities involved in RAS metabolism in NMU-induced breast cancer animals has been also analyzed. We observed that APA is increased in all the studied groups; therefore, this effect could be due to tumor rather than the diet.…”
Section: Discussionmentioning
confidence: 99%
“…5 Also, local RAS can participate in various pathological processes such as cancer. 6,7 It is known that Ang II regulates cell turnover by promoting both cell proliferation and programmed cell death through differential actions via the AT1 and AT2 receptors, 8 and also it is known that AT1 and AT2 receptors are expressed in breast cancer. However, Ang II is not the only element of RAS that participates in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Previous studies indicated that ACE inhibitor could lower the breast cancer risk. 29 In recent years, more and more publications suggested that the ACE I/D polymorphism is related to breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%